Excavation of Education Fund Sources at SD Negeri Samirono Yogyakarta (Penggalian Sumber Dana Pendidikan di SD Negeri Samirono Yogyakarta) - Tiarani Mirela; Erni Munastiwi; Amiruddin Amiruddin (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to describe the excavation of educational funding sources consisting of 1). Exploration of sources of education funds through the Government 2). Exploring education funding sources through parents/school committees and 3). Exploring sources of education funds through the community. This research is a qualitative type with a descriptive approach that collects data by observing, interviewing and documenting. The results of this study stated that SD N Samirono Yogyakarta did not procure sources of funds from other sources, only relied on funds from the government, but SD N Samirono Yogyakarta tried to meet the needs of schools with minimal and sufficient funds but this was still felt by the school to be lacking and was just planned to collaborate with the school committee at SD Negeri Samirono Yogyakarta. So that we can know that the procurement of good and structured sources of funds will help realize the implementation of the educational process in realizing educational goals effectively and efficiently.Keywords: Education Financing, Finance, Education Fund SourcesPenelitian ini bertujuan untuk mendeskripsikan penggalian sumber dana pendidikan yang terdiri dari 1). Penggalian sumber dana pendidikan melalui Pemerintah 2). Penggalian sumber dana pendidikan melalui orang tua/komite sekolah dan 3). Penggalian sumber dana pendidikan melalui masyarakat. Penelitian ini berjenis kualitatif dengan pendekatan deskriftif yang melakukan pengumpulan data dengan observasi, wawancara dan dokumentaasi. Hasil penelitian ini menyatakan SD N Samirono Yogyakarta tidak melakukan pengadaan sumber dana dari sumber lainnya hamya mengandalkan dana dari pemerintah saja, namun SD N Samirono Yogyakarta berusaha mencukupi kebutuhan sekolah dengan dana seadanya dan secukupnya akan tetapi hal ini masih dirasa kurang oleh pihak sekolah dan baru direncanakan untuk mengadakan kerjasama dengan pihak komite sekolah di SD Negeri Samirono Yogyakarta. Sehingga dapat kita ketahui penggadaan sumber dana yang baik dan terstruktur akan membantu mewujudkan pelaksaan proses pendidikan dalam mewujudkan tujuan pendidikan secara efektif dan efesien.Kata Kunci: Pembiayaan Pendidikan, Keuangan, Sumber Dana Pendidikan